Ornithological observations in Southern Peary Land, North Greenland, 1973 - Meltofte, Hans (Meddelelser om Grønland, 1976)
The present paper is a report on one summer’s work at Jørgen Brønlund Fjord in Southern Peary Land, the Northern most part of Greenland. The main project was a census of breeding waders and observations of their breeding biology. It was found that some species, e.g. the waders, breed earlier around Jørgen Brønlund Fjord than in most of the Arctic, but in small numbers. This is discussed in relation to the climatic conditions, especially the extremely small amount of snow. Furthermore an avifaunistic status is given, and discussed in relation to earlier reports. It was found that Branta bernicla hrota has disappeared from this part of Greenland since the first part of the century, and that Calidris canutus has increased in number. Methods of wader censuses are discussed.